2021
DOI: 10.48550/arxiv.2104.02553
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Large-scale Sustainable Search on Unconventional Computing Hardware

Kirill P. Kalinin,
Natalia G. Berloff

Abstract: Since the advent of the Internet, quantifying the relative importance of web pages is at the core of search engine methods. According to one algorithm, PageRank, the worldwide web structure is represented by the Google matrix, whose principal eigenvector components assign a numerical value to web pages for their ranking. Finding such a dominant eigenvector on an ever-growing number of web pages becomes a computationally intensive task incompatible with Moore's Law. We demonstrate that special-purpose optical m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 69 publications
(113 reference statements)
0
7
0
Order By: Relevance
“…Calculating the principal eigenvector is also required in other fields such as social network analysis, bibliometrics, recommendation systems, DNA sequencing, bioinformatics, and distributed computing systems. [194][195][196] There are numerous applications of PageRank to chemistry and engineering sciences networks to investigate and analyse complex systems. As systems grow in size and complexity, the interactions between their networks and subnetworks can become increasingly complicated and difficult to track.…”
Section: Finding the Principal Eigenvectormentioning
confidence: 99%
See 4 more Smart Citations
“…Calculating the principal eigenvector is also required in other fields such as social network analysis, bibliometrics, recommendation systems, DNA sequencing, bioinformatics, and distributed computing systems. [194][195][196] There are numerous applications of PageRank to chemistry and engineering sciences networks to investigate and analyse complex systems. As systems grow in size and complexity, the interactions between their networks and subnetworks can become increasingly complicated and difficult to track.…”
Section: Finding the Principal Eigenvectormentioning
confidence: 99%
“…[198] Recent research has shown that optical systems can provide significant advantages for calculating the principal eigenvector. [196] By choosing appropriate control parameters for these optical systems, the steady state of optical networks can be used to solve an eigenvalue maximization problem. [199] This results in the identification of the energy state dictated by the signs of the eigenvector corresponding to the largest eigenvalue of the interaction matrix, that is, the principal eigenvector.…”
Section: Finding the Principal Eigenvectormentioning
confidence: 99%
See 3 more Smart Citations